After the Long Walk Home…the Gendered Rural Safety Net. (June 2023) - Nathan, Dev; Rahul S.,; Kelkar, Govind
In the absence of adequate social security for migrant workers, the recession forced the mass exodus of millions of circular migrants supported by their rural households of largely left-behind women. Our article looks at what happened after that. How did the returned migrants manage to survive and retain their capacity to work till they were required back in urban employment? This article argues that gendered rural households functioned as safety nets in the severe recession in the Indian economy which highlights the weakness in the state policy and lack of resources in the wake of the COVID-19 pandemic. They were safety nets not only for workers directly working in food value chains but also for reverse migrants. Overall, the recession did not just result in a temporary loss of income but also increased inequality and strengthened the oligopoly structure of the Indian economy.